Phase Angle Cut-Off Points and Their Association With Sarcopenia and Frailty in Adults of 50–64 Years Old and Older Adults in Mexico City - Rosas-Carrasco, Oscar; Ruiz-Valenzuela, Roxana E.; López-Teros, Miriam T. (Frontiers in Medicine, 2021)
Background: In recent studies, the usefulness of the phase angle (PA) to assess geriatric conditions such as sarcopenia and frailty has been evaluated. However, there are no useful cut-off points for clinical research and/or practice. Objective: To analyze PA cut-off points associated with sarcopenia and frailty in adults of 50-64 years old and older adults in Mexico City. Design: Cross-sectional analysis of the FraDySMex cohort study (Frailty, Dynapenia, and Sarcopenia in Mexican Adults). Setting and Participants: 498 people were included, 78.7% women, aged 71.1 ± 9.5 years. Methods: The sarcopenia measurements were made according to the European Working Group on Sarcopenia in Older People (EWGSOP) (2019) (by dynamometer to evaluate hand grip strength and dual energy X-ray absorptiometry (DXA) for appendicular muscle mass), and the frailty through the physical frailty phenotype with cut-off points adjusted to the Mexican population. The PA was evaluated by bioelectrical impedance analysis (BIA), tetrapolar to 50 Hz, other variables such as socio-demographic, comorbidity, cognitive status, and functional dependence were evaluated. Results: The prevalence of frailty was 10.6% and sarcopenia 10.0%. The mean of the PA was 4.6° ± 0.70°. The PA cut-off point for frailty in adults 50 to 64 years was ≤4.3° [sensitivity (S) = 91.95%, specificity (Sp) 66.77%, AUROC (Area Under the Receiver Operating Characteristic) curve = 0.9273 95% CI (0.8720-0.9825)]; the PA cut-off point for sarcopenia was ≤4.3 [S = 91.95%, Sp = 66.77%, AUROC = 0.9306 95% CI (0.8508-1.000)]. The PA cut-off for frailty in adults ≥ 65 years was ≤4.1° [S = 72.37%, Sp 71.43%, AUROC = 0.7925 95%, CI (0.7280-0.8568)] for sarcopenia was ≤4.1° [S = 72.76%, Sp 73.81%, AUROC = 0.7930 95% CI (0.7272-0.8587)]. These cut-off points showed a significant association between PA with frailty (OR 4.84; 95% CI 2.61-8.99) and sarcopenia (OR 8.44; 95% CI 3.85-18.4) after adjusted by age, sex, BMI, comorbidity index and cognitive impairment. Conclusions and Implications: These cut-off points of PA could be useful for the screening of sarcopenia and frailty in Mexican adults of 50 years and older in centers that have BIA.